Is There an Association between Sodium-Based Additives and Total Sodium Content of Foods? - Carla Almeida; Eduarda Lopes; Patrícia Padrão (Proceedings)
Background and objectives: Excessive sodium intake is a major public health issue. Despite the large use of sodium-based additives, their contribution to sodium content is unknown. This work aims to study the association between the use of sodium-based additives and the sodium content of foods sold by a market-leading Portuguese food retail company. Methods: White-label pre-packaged foods and fresh products were included in this study. The salt content of pre-packaged foods was supplied by the company and converted to sodium. The sodium content of non-industrially packaged foods was estimated through food composition tables. Foods were categorized based on the World Health Organization sodium benchmarks. The sodium-based additives on the label’s ingredient list were identified according to Regulation (EU) No. 1129/2011 and counted. Non-parametric tests (n > 5) were used to test the median sodium content (mg/100 g) (minimum, maximum) according to the use of sodium-based additives. Results: A rising sodium content was observed from 0 [56.7 mg (0, 39880)] to ≥ 3 additives [520 mg (60, 2080)] (n = 2451, p < 0.001). A total of 12 categories and 13 subcategories were analyzed. The use of sodium-based additives was associated with higher sodium content for the following categories (a) and subcategories (b): Confectionary (a) (p < 0.001), Chocolates/candies (b) (p < 0.001), Savory snacks (a) (p < 0.001), Salted biscuits (b) (p = 0.027), Fresh (a) and Processed meat/fish (a) (p < 0.001), Processed fruit/vegetables/legumes (a) (p < 0.001), Canned vegetables/legumes (b) (p < 0.001), Ices (a) (p = 0.006), Ready meals (a) (p = 0.030), Composite ready meals (b) (p = 0.001), Cookies (b) (p = 0.007), Cakes (b) (p = 0.022). The use of sodium-based additives was associated with lower sodium content for Beverages (a) (p = 0.002), Fish (heat treated) (b) (p = 0.020), and Pastries (b) (p = 0.045). Non-significant differences were observed for 4 categories and 5 subcategories. Discussion: A positive association between the use of sodium-based additives and the sodium content was observed. Inconsistent results were found across categories, suggesting the need for a deeper analysis of the foods included in each category or subcategory.